An anaplastic pleomorphic xanthoastrocytoma with periventricular extension: An autopsy case report and review of the literature. Issue 5 (23rd June 2020) - Matsumoto, Yuki; Kobayashi, Mikiko; Shingu, Kunihiko; Tateishi, Ayako; Ohya, Maki; Sano, Kenji; Negishi, Tatsuya; Shigeto, Shohei; Kobayashi, Tatsuya; Hara, Yosuke; Kakizawa, Yukinari; Kanno, Hiroyuki
Abstract : Pleomorphic xanthoastrocytomas (PXAs) are rare low‐grade astrocytic tumors that typically present as superficial nodular cystic tumors of the cerebrum attached to the leptomeninx. Histologically, they are pleomorphic, hypercellular glial neoplasms. Despite the presence of microscopic pleomorphism, patients' postoperative prognosis is generally good. Anaplastic PXAs (APXAs) have a high mitotic index and patients with APXAs have a worse prognosis than patients with PXAs. Here, we report an autopsy case of APXA initially diagnosed as PXA. After gross total resection, the tumor recurred and was diagnosed as an APXA; thereafter, the patient died. An autopsy revealed that the tumor had relapsed at the primary site and had spread to the leptomeningeal space while concurrently invading the cerebrum including the periventricular area forming multifocal lesions. The histological findings of the autopsy were similar to those for epithelioid glioblastoma (EGBM) and small cell glioblastoma (SCGBM). In particular, the periventricular area with multifocal lesions was composed of SCGBM‐like cells. It has been shown that multifocal lesions are frequently identified in patients with SCGBM. This is the first histopathologically confirmed case of APXA‐related tumor presenting with periventricular extension and multifocal lesion formation. The periventricular extension might be a feature of PXAs and APXAs. However, suspected periventricular spread on imaging in past cases of PXAs and APXAs might instead represent the malignant transformation of these tumors to glioblastoma‐like high‐grade tumors, which often show SCGBM‐like histological patterns.